Royal repertories G. J. Dowler asks which Ashton and MacMillan pieces are in repertory, and why - Dowler, Gerald (Dance Books Ltd., Alton,Hampshire (UK), 1998)
PALABRAS CLAVE: Frederick Ashton, Kenneth MacMillan, Royal Ballet, repertory.